A systematic database for microbial data collection management - Norsyahima Azizi,; Suhaila Sulaiman,; Farah Nini Othman,; Lee, Yang Ping (Penerbit Universiti Kebangsaan Malaysia, 2022)
Microbiology research is one of the research fields that deal with a huge volume of microbial culture collection data which needs to be preserved, due to its importance as a key resource center for obtaining, identifying, producing, preserving, cataloging, and distributing culture data of various microbes. Currently, the collection and storing of microbial culture data is performed manually via various data transfers into record books, logbooks, or spreadsheets. However, the manual process seems to be impractical as it is highly prone to human error and time-consuming, aside from the struggle of managing and retrieving the data. Therefore, to address this issue, we have successfully designed and developed a customized database for microbial data collection that allows users to store, access, visualize and retrieve information in a single platform. The agile development approach has been implemented during the software development process allowing more flexibility during the development phase yet managing to fulfill the functional requirements of the end-users. The front end is created using the Bootstrap framework, an open-source and powerful platform for developing user-friendly web pages and web applications. It is connected to the back-end MySQL database as a relational database management system to organize structured data. As a result, the developed microbial culture collection has eliminated manual data entry and accelerated the data retrieval process. The platform is a one-stop platform for microbiologists when dealing with microbial culture collection data.